Parental participation and parents’ support: effects on mathematics achievement, 2018 national assessment of learning, Mexico - Hernández-Padilla, Eduardo; Bazán-Ramírez, Aldo; Bazán-Ramírez, Wilfredo; Solano-Gutierrez, Juan (Frontiers in Psychology, 2023)
The relationship between family involvement in students' academic activities, their learning, and academic achievement has been widely studied. Two different types of family involvement are recognized: parental participation, which is linked to activities implemented by the school, and parental support, which occurs at home and has to do with the family's educational practice. This study analyzed the influence of socioeconomic level on parental support at home, parental participation in school activities, and family and school factors associated with student learning in mathematics. The database of 104,973 third-year high school students (50.1% female and 49.9% male) from the 2018 assessment of academic achievement in mathematical thinking was considered. Path analysis was employed in structural equation modeling, where a general model of parental support was proposed to compare the learning of students from the lowest quartile and those from the highest socioeconomic level; the model presented a good fit for each group. The models used showed acceptable adjustments in some criteria; in these models, there were positive and significant associations between parental schooling and socioeconomic level and achievement in mathematics. The results obtained are consistent with the findings of other studies in which parental support, mediated by socioeconomic status, significantly influences student learning.